Research - the African way! Bless, C & Higson-Smith, C (1995) Fundamentals of social research methods: An African perspective. (2nd edition). Cape Town: Juta. - Tredoux, Colin (PINS-Psychology in Society, 2026)
The bold title of this book suggests a local alternative in a market that is well traded, and firmly under the control of North American publishing houses. There are many good methodology texts on offer, and new ones need to provide something quite distinctive if they are to elbow their way into undergraduate courses at local universities. This one seems to offer an African perspective on what other texts treat as universal.